Plaque-removal efficacy of three types of dental floss - Witjaksono, Widowati; Tin, Myo Han; Khalid, Mohd Arif Alwan; Abdullah, Abrar (2014)
Objectives: The objective of the study was to evaluate the plaque removing efficacy of three types of floss, which are superfloss, waxed floss, and sewing thread. Materials and method: A cross-over study design was applied where 15 subjects were undergone three regimen of dental floss with the duration of one week each, starting from September 2013 to November 2013. The subjects used the superfloss (SF) for one week, and then the plaque removing efficacy of the floss was measured using the modified Rustogi Navy plaque Index (RMNPI), which emphasizes on the interproximal area. After that, the subjects were free from any flossing for one week before starting with next regimen. These steps were repeated for waxed floss (WF) and also sewing thread (ST). Results: In this study, mean (±SD) plaque score of SF, WF, and ST are 0.675 (±.099), 0.477 (±.098) and 0.197 (±.026) respectively; those of before flossing are 0.680 (±.100), 0.660 (±.106) and 0.685 (±.097) respectively; those of after flossing are, 0.464 (±.099), 0.471 (±.107) and 0.496 (±.093) respectively; and the difference between before and after flossing are 0.215 (±.009), 0.213 (±.009) and 0.163 (±.0127) respectively. There were no statistically significance differences between plaque score before and after of the three flosses. However, plaque score differences between those flosses were significant (p<0.05), with SF and WF has higher efficacy compare to ST. Inter-quartile ranges (IQR) values of those flosses were (0.010), (0.013) and (0.023) respectively. Conclusion: Superfloss and waxed floss have higher plaque removal efficacy in comparison to sewing thread. There are no significant differences in plaque removal efficacy between superfloss and waxed floss. However, sewing thread is also reliable to remove plaque in time of unavailability of commercial floss and in socioeconomically disadvantages individuals. Key words: dental plaque, superfloss, waxed floss, sewing thread, efficacy